Research handbook on interdisciplinary approaches to law and religion - Sandberg, Russell; Doe, Norman; Kane, Bronach; Roberts, Caroline (Edward Elgar Publishing, 2019)
"Law and religion, as a subdiscipline of law, has gained increasing attention in recent years. However, the complex relationship between law and religion cannot be fully understood with reference to legal research alone. This Research Handbook includes provocative chapters from experts on a range of concepts, perspectives and theories, drawing on a variety of disciplines, which can be used to further law and religion scholarship. Featuring chapters written by authors from a diverse range of backgrounds, the Handbook focuses on five main perspectives on law and religion: historical, philosophical, sociological, theological and comparative. Each chapter provides a new way of looking at law and religion which can complement and enhance a doctrinal legal understanding of the topic. Crucially, this Handbook also highlights the importance of recognising doctrinal legal study as an approach in itself, which will shape research questions and outputs accordingly. Providing an engaging and thoughtful introduction to the range of interdisciplinary approaches that can be taken to law and religion, this Handbook will be of interest to scholars in law and religion, theologians, sociologists, legal historians and political scientists. It will provide a rich foundation for future interdisciplinary research in this important area of study"--